Biofilm model systems for root canal disinfection: a literature review. (20th December 2018) - Swimberghe, R. C. D.; Coenye, T.; De Moor, R. J. G.; Meire, M. A.
Abstract: The aim of this review was to present an overview of laboratory root canal biofilm model systems described in the endodontic literature and to critically appraise the various factors that constitute these models. The electronic databases MEDLINE, Web of Science and EMBASE were searched up to and including December 2016 to identify laboratory studies using endodontic biofilm models. The following search terms were used in various combinations: biofilm, root canal, in vitro, endodontic, bacteria, root canal infection model, colony‐forming unit. Only English papers from journals with an impact factor were selected. The records were screened by two reviewers, and full‐text articles were assessed according to pre‐defined criteria. The following data were extracted from the included studies: the microbial composition of the biofilm, the substrate, growth conditions, validation and quantification. Seventy‐seven articles met the inclusion criteria. In the majority (86%) of the studies, a monospecies biofilm was cultured. In two studies, a dual‐species biofilm was grown; others cultivated a multispecies biofilm, containing at least three species. Enterococcus faecalis was the most frequently used test species (in 79% of all studies, 92% of the monospecies studies). Four studies used an inoculum derived directly from the oral cavity. Human dentine was the most frequently used substratum (88% of the studies). Incubation times differed considerably, ranging from one to seventy days. The most common quantification method (in 87% of the studies) was bacterial culturing, followed by microscopy techniques. The variation in laboratory root canal biofilm model systems is notable. Because of substantial variation in experimental parameters, it is difficult to compare results between studies. This demonstrates the need for a more standardized approach and a validated endodontic biofilm model.